CDG: Managing in China's Economic Transformation - CHUA, Roy (Institutional Knowledge at Singapore Management University, 2010)
China Data Group (CDG) is a leading business processes outsourcing company based in Beijing, China. Roc Yang, Chairman of CDG had to confront a dilemma when he discovered that one of his senior managers gave a gift to a potential client in an effort to win a large business deal. Although this practice was pervasive in the China business context characterized by heavy reliance on personal relationships or guanxi, it went against the founding principles of CDG - professionalism and service quality. Yang had to decide where to draw the line between adherence to principles of professionalism and local norms in a country caught in the midst of rapid economic transformation.